Clearance of maternal barriers by paternal miR159 to initiate endosperm nuclear division in Arabidopsis - Youshang Zhao (Nature Portfolio, 2018)
Seed development in plants is triggered by entry of sperm to the ovule. Here, Zhao et al. uncover miR159 as a paternal-trigger of seed development that is transmitted to the central cell where it represses expression of maternal targets to promote nuclear division in the endosperm.